TAX PLANNING MENGHADAPI KENAIKAN TARIF PPN: STUDI PADA WAJIB PAJAK DI FLORES TIMUR - Danny Wibowo (Management and Sustainable Development Journal, 2025)
This research aims to tax planning of Taxable Entrepreneurs against changes in Value Added Tax tax regulations. This research uses a descriptive qualitative approach where the process of describing the research area is organized in narrative form. Data collection used an interview method conducted with Taxable Entrepreneurs in East Flores. The results of this study reveal that an increase in the VAT rate is very problematic because it can impact consumer behaviour. However, informants do not ignore tax regulations; they understand that violating taxes can hurt their business continuity. This finding presents the efforts of taxable entrepreneurs in East Flores to maintain their business sustainability using tax planning. Other findings regarding the environmental perspective formed from the level of experience and age and the encouragement of the social community also stimulate taxpayer behaviour in assessing changes in tax regulations, especially related to VAT rates.